ANALYTICAL STUDY OF THE DELAY INTRODUCED AS A RESULT OF ENCRYPTION/DECRYPTION OF VOICE TRANSMITTED OVER A VPN NETWORK: ANALYTICAL STUDY OF THE DELAY INTRODUCED AS A RESULT OF ENCRYPTION/DECRYPTION OF VOICE TRANSMITTED OVER A VPN NETWORK - Denev , Daniel (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The purpose of this article is to evaluate the impact of the decoding/encoding process on the IP based voice transfer. A short analysis of the decoding/encoding algorithm has been made. Using the result from the conducted analysis evaluation model has been created. A series of simulations have been performed and the results are represented in graphical form.